(untitled) (Research, Society and Development, 2023)
The work presented for now aimed to evaluate, through a bibliographical review, the role of the physiotherapist in the early mobilization of patients with COVID-19. For this, a systematic review was carried out Articles, books, dissertations, guidelines and theses available in the following online databases: Scientific Electronic Library Online (SciELO), Publisher Medline (PubMed), Latin American and Caribbean Literature in Life Sciences Saúde (Lilacs), Physiotherapi Evidenci Database (PEDro) in the format of scientific articles, theses and dissertations, related to the subject within the inclusion and exclusion criteria, published in the period between 2020 and 2021, in Portuguese, English and Spanish. The search strategy was based on the PICO method using Boolean descriptors and operators: “Physiotherapy”, “Early mobilization”, “Mechanical ventilation”, “Critical patients”, “ICU” and “Rehabilitation”. During the searches, 123 citations were found which, after excluding duplicates, totaled 61 citations. Title and abstract analysis was performed, 40 citations were excluded and 21 studies were selected for full reading. 10 studies were excluded for not meeting the inclusion criteria, and 11 studies were included in the review. It concluded with the development of the work that physiotherapists had and still have the role of providing interventions for mobilization, exercise and rehabilitation, especially for patients at risk of developing functional decline.